Perancangan Sistem Informasi Peralatan Menggunakan Object Oriented Analysis and Design Model Rational Unified Proces - Encep Supriatna; Rima Rima (Masoem University, 2022)
Equipment management at the Al Ma'soem Bandung Foundation (YAB) is still done manually, giving rise to several obstacles including difficulty controlling the availability and condition of equipment in units, difficulty knowing prices and acquisition dates if needed at any time, and difficulty detecting warranty date and service schedule for electronic equipment/vehicles that require routine maintenance. To streamline access to equipment information, it is necessary to design a website-based equipment information system. The method used is the Object Oriented Analysis and Design Rational Unified Process model with the Unified Modeling Language system modeling tool. With a website-based equipment information system, access to equipment information at the Al Ma'soem Bandung Foundation will be easier for various interested parties.